Comparative effects of different balance-training-progression styles on postural control and ankle force production: A randomized controlled trial - Cug, M.; Duncan, A.; Wikstrom, E. (Journal of Athletic Training, 2016)
Context: Despite the effectiveness of balance training, the exact parameters needed to maximize the benefits of such programs remain unknown. One such factor is how individuals should progress to higher levels of task difficulty within a balance-training program. Yet no investigators have directly compared different balance-training-progression styles.